2020
DOI: 10.1161/jaha.119.015318
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Cause of Early Fontan Complications: Does the Lymphatic Circulation Play a Role?

Abstract: Background Recent studies suggest that lymphatic congestion plays a role in development of late Fontan complications, such as protein‐losing enteropathy. However, the role of the lymphatic circulation in early post‐Fontan outcomes is not well defined. Methods and Results This was a retrospective, single‐center study of patients undergoing first‐time Fontan completion from 2012 to 2017. The primary outcome was early Fontan complication ≤6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 17 publications
5
60
0
Order By: Relevance
“…2,8 The rate of postoperatively thoracic lymphatic perfusion pattern abnormalities in our study is comparable to those reported by Ghosh et al before Fontan surgery. 13 Ghosh et al reported normal thoracic lymphatic perfusion pattern preoperatively in 32% of patients compared with 29% postoperatively in our cohort. While a minority of 15% developed early complications in the absence of preoperative abnormalities of thoracic lymphatic perfusion pattern, 13 none of our patients with normal lymphatic perfusion pattern postoperatively developed early Fontan complications.…”
Section: Discussionsupporting
confidence: 43%
“…2,8 The rate of postoperatively thoracic lymphatic perfusion pattern abnormalities in our study is comparable to those reported by Ghosh et al before Fontan surgery. 13 Ghosh et al reported normal thoracic lymphatic perfusion pattern preoperatively in 32% of patients compared with 29% postoperatively in our cohort. While a minority of 15% developed early complications in the absence of preoperative abnormalities of thoracic lymphatic perfusion pattern, 13 none of our patients with normal lymphatic perfusion pattern postoperatively developed early Fontan complications.…”
Section: Discussionsupporting
confidence: 43%
“…Systemic embolism is more likely to occur in the subgroup of Fontan patients with plastic bronchitis, but not in those with protein losing enteropathy. Indeed, such patients exhibit frequent lymphatic abnormalities even before Fontan completion (9). Very frequently Fontan patients with plastic bronchitis have an additional problem of the thoracic duct (obstruction, occlusion, absence).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathophysiology behind PB in CHD patients is not fully understood. However, recent findings attribute a central role to a pressured and morphologically changed lymphatic system ultimately resulting in lymphatic leakage into the airways [95][96][97][98]. Similarly to PLE, the lymphatic system in patients with PB may be thought to be challenged on multiple fronts.…”
Section: Plastic Bronchitismentioning
confidence: 99%
“…The elevated CVP impedes lymphatic return and causes lymphatic congestion. Additionally, the changed lymphatic architecture with the existence of multiple abnormal collaterals and larger more dilated lymphatic vessels may increase risk of leakage, with protein-rich fluid leaking into the low-pressure environment of the airways [30,31,98,99]. Following leakage, as the final step, an inflammatory reaction, preceded by concurrent respiratory infections or individual abnormalities in the inflammatory response causes the fibrin in the lymphatic fluid to cross-link, producing the solid casts pathognomonic of PB (Fig.…”
Section: Plastic Bronchitismentioning
confidence: 99%
See 1 more Smart Citation